Relationship between internet use intensity and quality of life in chronic patients during the COVID-19 pandemic: The role of physical exercise and health insurance - Wang, Yangyang; Xu, Jian; Xie, Tian (Frontiers in Public Health, 2022)
The intensity of human internet use has increased substantially during the COVID-19 pandemic, severely impacting the well-being of chronic patients. This study aimed to explore the underlying mechanism of the relationship between internet use intensity and quality of life in chronic patients. This study used cross-sectional data from China Family Panel Studies (CFPS) during the COVID-19 Pandemic in 2020. The results showed that the internet use intensity had a significant positive association with quality of life among chronic patients. And such association has been found in both urban and rural samples. The mediating effect of physical exercise reached 11.27% in the relationship between internet use intensity and quality of life among chronic patients. Furthermore, health insurance positively moderated this relationship. In both rural and urban governance, public health agencies should promote the "Internet plus health care" program to improve health insurance and physical activity literacy, thus providing a higher level of quality of life for patients with chronic diseases during the COVID-19 pandemic.